Nuclear Morphology Measurements with Angle-Resolved Low Coherence Interferometry For Application To Cell Biology And Early Cancer Detection. (2011) - Wax, Adam; Chalut, Kevin J.
Abstract : The study of intact, living cells using non-invasive optical spectroscopic methods offers the opportunity to assess cellular structure and organization in a way that is not possible with commonly used cell biology imaging techniques. We have developed a novel spectroscopic technique for diagnosing disease at the cellular level based on using low-coherence interferometry (LCI) to detect the angular distribution of scattered light. Angle-resolved LCI (a/LCI) combines the ability of LCI to isolate scattering from sub-surface tissue layers with the ability of light scattering spectroscopy to obtain structural information on sub-wavelength scales. In application to examining cellular structure, a/LCI enables quantitative measurements of changes in the size and texture of cell nuclei. These quantitative measurements are characteristic of different pathological states. The capabilities of a/LCI were demonstrated using a clinical system that can be applied in endoscopic surveillance of esophageal tissue, producing high sensitivity and specificity for detecting dysplastic tissues in vivo . Experiments with in vitro cell samples also show the utility of a/LCI in observing structural changes due to environmental stimuli as well as detecting apoptosis due to chemotherapeutic agents.